CDKN2A Determines Mesothelioma Cell Fate to EZH2 Inhibition - Pinton, Giulia; Wang, Zhuo; Balzano, Cecilia; Missaglia, Sara; Tavian, Daniela; Boldorini, Renzo; Fennell, Dean A.; Griffin, Martin; Moro, Laura (Frontiers in Oncology, 2021)
Malignant pleural mesothelioma is an aggressive cancer, heterogeneous in its presentation and behaviour. Despite an increasing knowledge about molecular markers and their diagnostic and prognostic value, they are not used as much as they might be for treatment allocation. It has been recently reported that mesothelioma cells that lack BAP1 (BRCA1 Associated Protein) are sensitive to inhibition of the EZH2 (Enhancer of Zeste Homolog 2) histone methyltransferase. Since we observed strong H3K27me3 (histone H3 lysine 27 trimetylation) immunoreactivity in BAP1 wild-type mesothelioma biopsies, we decided to characterize in vitro the response/resistance of BAP1 wild-type mesothelioma cells to the EZH2 selective inhibitor, EPZ-6438. Here we demonstrate that BAP1 wild-type mesothelioma cells were rendered sensitive to EPZ-6438 upon SIRT1 (Sirtuin 1) silencing/inhibition or when cultured as multicellular spheroids, in which SIRT1 expression was lower compared to cells grown in monolayers. Notably, treatment of spheroids with EPZ-6438 abolished H3K27me3 and induced the expression of CDKN2A (Cyclin-Dependent Kinase Inhibitor 2A), causing cell growth arrest. EPZ-6438 treatment also resulted in a rapid and sustained induction of the genes encoding HIF2α (Hypoxia Inducible Factor 2α), TG2 (Transglutaminase 2) and IL-6 (Interleukin 6). Loss of CDKN2A is a common event in mesothelioma. CDKN2A silencing in combination with EPZ-6438 treatment induced apoptotic death in mesothelioma spheroids. In a CDKN2A wild-type setting apoptosis was induced by combining EPZ-6438 with 1-155, a TG2 selective and irreversible inhibitor. In conclusion, our data suggests that the expression of CDKN2A predicts cell fate in response to EZH2 inhibition and could potentially stratify tumors likely to undergo apoptosis.